Climbing - Presson, Shelley (Camden, Me : Ragged Mountain Press, 2000)
This handbook covers both indoor climbing gyms and outdoor rock faces, offering advice to women pursuing climbing. It includes information on the physical requirements, beginner- to intermediate-level techniques, equipment, resources and safety.
AcknowledgmentsIntroductionChapter 1: Who Can Climb?A good match for womenWhat you'll get from climbing and why it might change your lifeHow and why they got startedChapter 2: Common Concerns and FearsI don't think I'm strong enough to climbAll of the climbers I see look like stick figures . . . but I'm heavyset!My family is worried that I'll get hurt. What can I tell them?I'm afraid of heightsThe idea of falling scares the wits out of meI don't want to embarrass myself, so I don't want to climb when people are aroundI'm too oldI have no one to go with: can I still try this?There's no climbing gym in my areaI'm pregnant: can I still climb?Chapter 3: Types of Climbing and Types of ClimbersTop rope climbingLead climbingBoulderingSport climbingTraditional climbingRock and its influence on types of climbingMorphologic climbingWhere does indoor climbing fit in?The rating systemChapter 4: Getting StartedWhere to goIf you decide to learn indoorsIf you decide to learn outsideChapter 5: Movement: The Really Fun Part of ClimbingBasic concepts of movementBasic techniques: face climbingImportance of restingBasic techniques: crack climbingChapter 6: Making ProgressWarm-up exercisesUsing specific holds and techniquesReading routesBecoming a competent belayerUnderstanding the mental side of climbingChapter 7: The GearHarnessChalk bagShoesBelay deviceGlovesLocking carabinerHelmetRopesA typical rack of gearChapter 8: Getting Fit, Staying Safe, and Having FunGetting strongerPreventing and handling injuriesAvoiding potential hazardsGetting yourself out of a bad situationUnderstanding first aidChapter 9: Next Steps: Taking Your Climbing FurtherLead climbingCompetition climbingClimbing holidaysClimbing with kidsChapter 10: ResourcesIndex
Includes bibliographical references and index.
Keywords: Rock climbing; Women athletes